Intellectual property and financing strategies for technology startups - Halt, Gerald B., Jr; Donch, John C., Jr; Stiles, Amber R.; Fesnak, Robert (Springer Science and Business Media : Springer, 2017)
This book offers a comprehensive, easy to understand guide for startup entities and developing companies, providing insight on the various sources of funding that are available, how these funding sources are useful at each stage of a company's development, and offers a comprehensive intellectual property strategy that parallels each stage of development. The IP strategies offered in this book take into consideration the goals that most startups and companies have at each stage of development, as well as the limitations that exist at each stage (i.e., limited available resources earmarked for intellectual property asset development), and provides solutions that startups and companies can implement to maximize their return on intellectual property investments. This book also includes a number of descriptive examples, case studies and scenarios to illustrate the topics discussed, and is intended for use by startups and companies across all industries. Readers will garner an appreciation for the value that intellectual property rights provide to a startup entity or company and will gain an understanding of the types of intellectual property rights that are available to companies and how to procure, utilize and monetize those intellectual property rights to help their company grow. Explains the relevance of intellectual property for startups and companies across the various stages of development and types of funding; Explores the benefits of protecting, managing and enforcing intellectual property so that companies can obtain the best possible commercial results from their IP ownership; Evaluates the role intellectual property plays in business development, raising funding capital, competitive strategy, product design and development, service delivery, marketing, and business expansion.
Includes index.
Keywords: Intellectual property.; New business enterprises -- Law and legislation.; New business enterprises -- Finance.; elektronické knihy; electronic books